2023
DOI: 10.1177/15357597231172322
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Physiology of Generalized Seizures: The 4 Horsemen of Absence Epilepsy

Abstract: [Box: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…36 Although rodent absence epilepsy models have face validity with respect to co-morbidities, developmental characteristics, and response to anti-seizure medications, their external validity has been questioned because of contradictory fMRI findings with human studies. 39 Indeed, human patients with absence seizures consistently exhibit decreased cortical bloodoxygen-level-dependent (BOLD) signal during seizures, 8,10,13,39 whereas rodents were found to have increased cortical BOLD signal. 36,40,41 However, McCafferty et al hypothesized that this discrepancy was secondary to the anesthetic agents given to rodents prior to the fMRI scan which altered their BOLD responses.…”
Section: Evidence From Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Although rodent absence epilepsy models have face validity with respect to co-morbidities, developmental characteristics, and response to anti-seizure medications, their external validity has been questioned because of contradictory fMRI findings with human studies. 39 Indeed, human patients with absence seizures consistently exhibit decreased cortical bloodoxygen-level-dependent (BOLD) signal during seizures, 8,10,13,39 whereas rodents were found to have increased cortical BOLD signal. 36,40,41 However, McCafferty et al hypothesized that this discrepancy was secondary to the anesthetic agents given to rodents prior to the fMRI scan which altered their BOLD responses.…”
Section: Evidence From Animal Studiesmentioning
confidence: 99%
“… 8 , 27 , 32 , 42 , 47 For instance, rodent studies of absence seizures identified EEG alterations that began up to 60 seconds prior to the first spike-wave discharge, and that coincided with a reduction in neuronal firing and altered behavior. 33 , 39 Similarly, multiple human fMRI studies have demonstrated early BOLD signal changes beginning at least five to ten seconds before seizure onset. 6 , 10 , 13 , 18 Although these findings were corroborated by Guo et al, they observed that fMRI changes only preceded absence seizures that were associated with impaired, but not spared, behavior.…”
Section: Seizure Time Course and Consciousnessmentioning
confidence: 99%